Fluoride Content in Instant Milk Formulas available in the Czech Republic - E. Oganessian; Z. Broukal; E. Lenčová; R. Ivančaková; J. Dušková (Czech Dental Chamber, 2008)
The aim of the study was to estimate the contribution of instant milk formulas (IMFs) manufactured by Nutricia, Nestlé and Hero available at local food market to the fluoride intake of infants in the Czech Republic. Fluoride content in IMFs dissolved in recommended bottled waters for infants has been determined in order to estimate the background fluoride intake when recommending fluoride supplementation. Totally 8 IMFs brands for children aged 1-3 months, 8 for 4-10 months and 6 for >10-months were involved. Formulae were dissolved either in deionised water or in three brands of bottled waters for infants containing 0.06, 0.15 and 0.56 ppm of fluoride. Fluoride content in dissolved IMFs was determined after HMDS-facilitated diffusion, using a fluoride ion specific electrode ELIT 8221 (Nico, USA) and an ionometer InoLab pH/ION 735P (WTW, Germany). During preparation stage of this study it was found that the employed microdiffusion sample processing [25] gave more than 97 % fluoride recovery among samples. Results: Fluoride concentrations ranged in IMFs: < 0.02 to 0.66 ppm when dissolved in deionised water, 0.04-0.34, 0.08 to 0.48 and 0.38 to 1.05 ppm when dissolved in infant bottled waters with 0.06, 0.15 and 0.56 ppm F, respectively. One brand of IMF, Sunar Complex Premium (Hero), was supplemented by fluoride (0.50 mg F/100 g of pulver). Its fluoride content after dissolution in deionised water and bottled waters with 0.06, 0.15 and 0.56 ppm F amounted to 0.87, 0.86, 1.04 nd 1.28 ppm, respectively. It is thus recommended to use low fluoride water for the reconstitution of that fluoride-supplemented brand of IMF.